Hand Eczema: Quality of Life and Disease Severity in an Outpatient Portuguese Population - Rui Pedro Santos; Laura Igreja; Cristina Resende; Teresa Pereira; Celeste Brito (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
Introduction: Hand eczema is a very common disease with a significant social and occupational impact. Objectives: To characterize a Portuguese outpatient population with hand eczema; to evaluate the impairment of the disease in quality of life (QoL); to relate the disease severity with QoL. Methods: The authors designed a prospective study. Information about atopy, psoriasis, occupational exposure and duration of disease, was recorded. The QoL was assessed by the DLQI questionnaire (Dermatology Life Quality Index) and the severity was assessed using the hand eczema severity index (HECSI). All participants were patch tested. Results: Eighty-five patients were included with a female predominance (78.8%). The median DLQI was 9.0. We found statistically significant differences in the variable HECSI between genders with greater impact in males. A significant positive correlation was found between HECSI and DLQI. DLQI and HECSI were independent of atopy, psoriasis or etiology. Increasing age significantly affects DLQI but not HECSI. Conclusions: Hand eczema has a significant impact in QoL. Although the disease is more prevalent among women it was found to be of greater severity among men. The QoL seems to be influenced by disease severity and increasing age but it was independent of the other studied variables.